2009
DOI: 10.1007/s00284-009-9477-9
|View full text |Cite
|
Sign up to set email alerts
|

Mycoparasitism of Endophytic Fungi Isolated From Reed on Soilborne Phytopathogenic Fungi and Production of Cell Wall-Degrading Enzymes In Vitro

Abstract: Antagonism of three endophytic fungi isolated from common reed (Phragmites australis) against eight soilborne pathogenic fungi was investigated on potato dextrose agar by light microscopy, scanning electron microscopy, and transmission electron microscopy. Inhibitory zones were not observed. The microscopical studies suggested that the endophytes inhibit growth of soilborne pathogens by means of coiling around hyphae and, after penetration, the degradation of hyphal cytoplasm. Since penetration of hyphae seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 35 publications
(33 reference statements)
1
26
0
Order By: Relevance
“…On the basis of microscopic observations, it was found that the hyphae of rYY‐11 could attach to and wind around the hyphae of S. sclerotiorum (Fig. 5a), indicating that rYY‐11 had an apparent mycoparasitism during the confrontation with S. sclerotiorum , which is consistent with previous studies (Cao et al. 2009).…”
Section: Resultssupporting
confidence: 90%
“…On the basis of microscopic observations, it was found that the hyphae of rYY‐11 could attach to and wind around the hyphae of S. sclerotiorum (Fig. 5a), indicating that rYY‐11 had an apparent mycoparasitism during the confrontation with S. sclerotiorum , which is consistent with previous studies (Cao et al. 2009).…”
Section: Resultssupporting
confidence: 90%
“…Fungal endophytes live asymptomatically within their host plants, obtaining nutrients and protection and being vertically or horizontally transmitted to the next plant generation (Rodriguez et al 2009). In exchange, many non-clavicipitaceous fungal endophytes protect their host plants from pathogens (Campanile et al 2007) by producing secondary metabolites (Schulz et al 1999) and/ or cell wall-degrading enzymes (mycoparasitism) (Cao et al 2009), by inducing systemic resistance (Vu et al 2006) or they may compete with pathogens for resources or niche space (Rodriguez et al 2009). Clavicipitaceous fungal endophytes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…), biological control of pests and disease (Cao et al . ; Zhang et al . ) and the production of metabolites of pharmacological interest, such as antibiotics, antioxidants and anticancer agents (Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the symbiotic relationship between plants and endophytic fungi, the plant gains competitive ability and resistance to biotic and abiotic factors due to the metabolites produced by the fungus, while these fungi benefit from the nutrients and shelter provided by the host plant (M€ uller and Krauss 2005). Several studies have demonstrated the relevance of endophytic fungi in the induction of host plant resistance (Dingle and McGee 2003;Kavroulakis et al 2007), plant growth promotion (Hamayun et al 2009b;You et al 2012), increased tolerance to abiotic stresses (Redman et al 2002;Khan et al 2012), biological control of pests and disease (Cao et al 2009;Zhang et al 2009) and the production of metabolites of pharmacological interest, such as antibiotics, antioxidants and anticancer agents (Zhang et al 2006;Chandra 2012;Radi c and Strukelj 2012;Budhiraja et al 2013).…”
Section: Introductionmentioning
confidence: 99%